Studying the Competencies of University Graduates Responding to Industrial Revolution 4.0 - Hoai, Tran Thi; Ba, Nguyen Thai (VNU Journal of Science: Education Research, 2020)
The Industrial Revolution 4.0 leads tomarketchanges in requirements for labours. The authors have studied domestic and international publications since 2014, interviewed 15 lecturers from Vietnam National University, Hanoi to propose the ten most necessary competencies of citizens adapting to human resources requirement of Industrial 4.0 Era. The proposed competencies include: (1) information technology skills, (2) creativity, (3) collaboration, (4) critical thinking, (5) problem solving, (6) communication, (7) emotion competence, (8) active and proactive learning capacity, (9) adaptability to changing work environment, (10) and entrepreneurship.